Prostorsko dojemanje in vzročnost nastopa čustev v luči glagolsko-samostalniških konstrukcij s predložnimi zvezami v slovenščini - Będkowska-Kopczyk, Agnieszka (Jezik in slovstvo, 2018)
The article investigates metaphorical verbal-nominal constructions consisting of prepositional phrases with nouns of emotion, and verbs expressing different types of abstract motion: caused motion (e.g., voditi koga v jezo lit. 'lead someone into anger'), autonomous motion (e.g., pasti v obup 'fall into despair'), and self-propelled motion (e.g., vstopiti v ljubezen lit. 'enter love'). These constructions express an event of emotional arousal and are motivated by the metaphor 'a change of state is a change of location'. By incorporating a cognitive syntactic analysis into the lexical analysis, the author sheds light on 1) the spatial basis of linguistic representations of emotion concepts and the event of emotional arousal, and 2) the conceptualisation of the event in terms of causality. The study confirms the embodied nature of metaphors expressing events in the abstract domain of emotion.
Keywords: čustva; glagoli premikanja; glagolsko-samostalniške konstrukcije; prostorsko dojemanje čustev; slovenščina; vzročnost